Evaluation of the Possibility of Calculating LD50 and LD10 Using a Modified Script in the R Environment - P. V. Shadrin (Регуляторные исследования и экспертиза лекарственных средств, 2025)
INTRODUCTION. The median lethal dose (LD50) and the low lethal dose (LD10) are critical parameters for the safety of medicinal products. Sometimes, the pharmacopoeial probit method (PM) fails to calculate the LD10 value, and the calculation result is obviously lower than the true value. In such cases, the use of other computational techniques is warranted.AIM. This study aimed to evaluate the potential of a script in the R environment as a tool for calculating the LD50 and LD10 of medicines.MATERIALS AND METHODS. This study compared the results of determining LD50 and LD10 using the spreadsheet-based pharmacopoeial PM and a modified script in the R environment (MS). The lm() function (linear regression model) was used to establish the relationships between the LD50 and LD10 values obtained using the PM and those calculated using the MS.RESULTS. A script originally developed by S. Young for LD50 calculation was modified and supplemented to simplify its use. The modification reduced the amount of input data required for calculation, added the ability to calculate LD10 values, and improved the visual clarity of the calculation results. Reducing the step size for the seq() function was shown to improve the output smoothness when the MS yielded a jagged mortality curve. The MS-derived LD50 values were within the confidence limits for the values obtained using the PM (P=0.95). The regression analysis confirmed the accuracy of the MS-based LD50 and LD10 calculations, which was demonstrated by a statistically insignificant systematic error, a significant dose dependence at P=0.999, and a high coefficient of determination (R2). If the PM underestimates LD10 values, the analyst should be guided by the LD50 and LD10 values calculated using the MS.CONCLUSIONS. The experimental data demonstrate the applicability of the MS for testing medicines. In some cases presented in the article, the custom R script offers an advantage over the current pharmacopoeial method. A tentative direction for further work may be the automation of the MS-based LD10 calculation.